DKI SIMULATION ANALYSIS OF THE INFLUENCE OF GOVERNMENT MINIMUM EXPENDITURE AND WAGE EXPENDITURE IN THE SIMULTANEOUS INDUSTRIAL SECTOR MODEL OF DKI JAKARTA PROVINCE - Wangke, Freddy (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
The purpose of the study was to determine the effect of increasing expenditure and increasing the minimum wage of the government in the simultaneous model of the industrial sector of DKI Jakarta province. The estimation model in the simultaneous model of the industrial sector of DKI province uses the 2 SLS (Two-Stage Least Squares) method. The simulation results of a 10% increase in the expenditure of the provincial government of DKI has resulted in an increase of investment of 4.72%, production growth of 0.19%, employment of 0.17%, an increase in production costs by 0.24%, and company profits increased by 0.10%. On the other hand, the simulation results of a 10% increase in the provincial minimum wage has resulted in a decrease in labor absorption by 0.55%, a decrease in production in the industrial sector has resulted in 0.21%, a decrease in investment by 0.07%, and a decrease in production costs by 0.04%. In conclusion, the increase in government spending often becomes the driving factor that provides incentives for entrepreneurs to expand their businesses, support industrial business development, and plan new investments. However, the increase in provincial minimum wages often hampers and decreases private business activities.